You Are What You Eat: A Genomic Analysis of the Gut Microbiome of Captive and Wild Octopus vulgaris Paralarvae and Their Zooplankton Prey - Roura, Álvaro; Doyle, Stephen R.; Nande, Manuel; Strugnell, Jan M. (Frontiers in Physiology, 2017)
The common octopus (Octopus vulgaris) is an attractive species for aquaculture, however, several challenges inhibit sustainable commercial production. Little is known about the early paralarval stages in the wild, including diet and intestinal microbiota, which likely play a significant role in development and vitality of this important life stage. High throughput sequencing was used to characterize the gastrointestinal microbiome of wild O. vulgaris paralarvae collected from two different upwelling regions off the coast of North West Spain (n=41) and Morocco (n=35). These were compared to that of paralarvae reared with Artemia for up to 25 days in captivity (n=29). In addition, the GI microbiome of zooplankton prey (crabs, copepod and krill) were also analysed to determine if the microbial communities present in wild paralarvae are derived from their diet. Paralarvae reared in captivity with Artemia showed a depletion of bacterial diversity, particularly after day 5, when almost half the bacterial species present on day 0 were lost and two bacterial families (Mycoplasmataceae and Vibrionaceae) dominated the microbial community. In contrast, bacterial diversity increased in wild paralarvae as they developed in the oceanic realm of both upwelling systems, likely due to the exposure of new bacterial communities via ingestion of a wide diversity of prey. Remarkably, the bacterial diversity of recently hatched paralarvae in captivity was similar to that of wild paralarvae and zooplankton, thus suggesting a marked effect of the diet in both the microbial community species diversity and evenness. This study provides a comprehensive overview of the bacterial communities inhabiting the gastrointestinal tract of O. vulgaris paralarvae, and reveals new research lines to challenge the current bottlenecks preventing sustainable octopus aquaculture.